A Target Tracking Application On Mobese Videos - Sevinc, A. Y.; Karabatak, Murat (Ieee, 2019)
The development of digital communication and image technologies is becoming increasingly widespread. The high resolution rates used in image technologies increased the quality of the recordings. These developments reveal the necessity of interpretation studies on digital images. Image processing applications were first created by the interpretation of still images. In order to achieve better image processing after the stages of obtaining, improving and decontamination of the image, certain features have been determined and highlighted. Nowadays, it continues with the processing and interpretation of moving images or videos. In recent studies, object tracking has gained importance in order to interpret visual inspection systems.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: object tracking; object recognition; vehicle tracking; feature template